Drug-drug interaction of paroxetine on olanzapine and initial dosage optimization in patients with major depressive disorder based on population pharmacokinetics - Zhang, Cun; Chen, Liang; Duan, Yin-Yin; He, Su-Mei; Tian, Ya-Li; Gao, Ying; Wang, Dong-Dong (Frontiers in Psychiatry, 2025)
ObjectiveOlanzapine is already used to treat patients with major depressive disorder; however, whether complex drug–drug interaction (DDI) has an effect on the pharmacokinetics of people using olanzapine and its initial dosage remains unknown. The present study aims to explore the effect of DDI on olanzapine.MethodsIn total, 72 patients with major depressive disorder were included for analysis. Potential physiological and biochemical indices and other drug combination information were collected to explore the effect of clinical olanzapine concentrations by building a nonlinear mixed effect (NONMEM) model and to further simulate the optimal olanzapine initial dosage by use of the Monte Carlo method in patients with major depressive disorder.ResultsWeight and combined use of paroxetine significantly affected olanzapine clearance. With the same weight, the clearance rates of olanzapine were 0.711:1 in patients with major depressive disorder with or without paroxetine. For the initial dosages, without paroxetine, the olanzapine administration dosages, 0.5 and 0.4 mg/kg/day were recommended for patients with major depressive disorder in the groups weighing 40 to 56 kg and 56 to 100 kg, respectively. With paroxetine, olanzapine administration dosages of 0.3 and 0.2 mg/kg/day were recommended for patients with major depressive disorder in the groups weighing 40 to 85 kg and 85 to 100 kg, respectively.ConclusionsThis has been the first case to establish olanzapine population pharmacokinetics in patients with major depressive disorder. In addition, the present study innovatively clarified that paroxetine affected olanzapine population pharmacokinetics and initial dosage in patients with major depressive disorder.